ANALYSIS OF CONSUMERBEHAVIOAR IN THE PURCHASE OF OPPO BRAND SMARTPHONE PRODUCTS IN STUDENST OF THE UNIVERSITY OF ECONOMIC AND BUSINESS FACULTY MUHAMMADIYAH - Aulia Aulia; Moh Aris Pasigai; Firdayanti Buhari (Jurnal Ilmu Manajemen Profitability, 2021)
This study aims to find out how the internal and external factors of consumer behavior in purchasing decisions for oppo brand smartphone Products on Studenst of the Faculty of Ekonomics and Business, University of Muhammadiyah Makassar (case study majoringin management class 2017). The type of research used with a qualitative approach. The data obtained is the result of interviews with 6 students majoring in management class of 2017. Internal factors of consumers behavior influence consumer decisions in purchasing Oppo Brand Smartphone prodyct of students majoring in management class 2017 Faculty of Economcs and Business, University of Muhammadiyah Makassar becauce the Oppo cellphone brand is good to use, not easily demaged, the camera is verry good, easy to get the nearest counter, high RAM, famaous cellphone brand, elegant designanda color. External factors of consumer behavior affect consumers in purchasing Oppo brand smartphone products for student students majoring in management class 2017 Faculty of Economcs and Business, University of Muhammadiyah Makassar because the Oppo cellphone is in accordance with family curture, friends who use the Oppo Cellphone, because theyare used to it and don’t reaplace it with the cellphone brand that other.